A congenital smooth muscle hamartoma masquerading as a reticulate vascular naevus. (13th June 2013) - Vivehanantha, S.; Browne, F.; Bowen, C.; Brundler, M.‐A.; Hughes, J.; Moss, C.; Taibjee, S. M.
Summary Smooth muscle hamartoma (SMH) is a benign congenital or acquired hamartomatous lesion comprising a dermal proliferation of smooth muscle bundles. We report a case of congenital SMH with an unusual clinical appearance. A 3‐year‐old girl presented with an asymptomatic atrophic linear lesion on the posterior surface of her right thigh, which had been present since birth. The striking resemblance to a vascular lesion initially led to the erroneous clinical diagnosis of atrophic reticulate vascular naevus. However, a skin biopsy showed typical features of SMH. To our knowledge, SMH with linear configuration has only been described in two previous cases, and there are no previous reports of SMH with such a marked resemblance to a vascular lesion.